2019
DOI: 10.1111/hae.13684
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychosocial determinants on caregivers’ burden of children with haemophilia (results of the BBC study)

Abstract: Introduction Caring for a child with haemophilia is burdensome and impacting on caregivers’ emotional and financial status. This paper assesses the impact of psychosocial determinants on caregivers’ burden across European countries. Methods This non‐interventional study enrolled caregiver/child dyads at haemophilia treatment centres (HTCs) using the “HEMOphilia associated CAregiver Burden scale” (HEMOCAB). Socio‐demographic characteristics and clinical data were collected. Results A total of 144 dyads from Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 33 publications
1
38
2
Order By: Relevance
“…Informal caregivers are often impacted by the emotional and financial burden of caregiving, including days lost from work, reduced number of hours worked or electing not to work at all. In one European study, two‐thirds of caregivers of children, mainly with severe HA, reported that haemophilia affected family life and 27% said haemophilia had an economic impact on the family 50 . Overall, these caregivers lost an average 8.4 days in the past 12 months due to their child's haemophilia.…”
Section: Methodsmentioning
confidence: 99%
“…Informal caregivers are often impacted by the emotional and financial burden of caregiving, including days lost from work, reduced number of hours worked or electing not to work at all. In one European study, two‐thirds of caregivers of children, mainly with severe HA, reported that haemophilia affected family life and 27% said haemophilia had an economic impact on the family 50 . Overall, these caregivers lost an average 8.4 days in the past 12 months due to their child's haemophilia.…”
Section: Methodsmentioning
confidence: 99%
“…The burden of caregivers is an important aspect to consider when assessing the management of PwHA. [19][20][21][22][23][24] Emicizumab, a bispecific, humanized, monoclonal antibody, bridges activated FIX and FX, thereby restoring the function of missing activated FVIII in PwHA. 25 It is approved for the prophylaxis of PwHA of all ages both with and without FVIII inhibitors in the United States, EU and other countries worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…One of the secondary objectives reported in this paper was to assess what clinical determinants impact on the burden of caregivers, stratified by severity, treatment modality, presence of inhibitors, joint health and chronic pain. The other objectives related to the impact of psychosocial determinants on caregiver burden, etc., are reported in a separate paper in this volume …”
Section: Introductionmentioning
confidence: 99%
“…The other objectives related to the impact of psychosocial determinants on caregiver burden, etc., are reported in a separate paper in this volume. 27 Clinical data about the children were collected by the haemophilia centre staff. This included type and severity of haemophilia, inhibitor status (current, ever, never), joint health (bleeding in the last 12 months, reduced range of motion, target joints), treatment regimen, surgery, chronic pain and other concomitant diseases.…”
Section: Introductionmentioning
confidence: 99%